Program Kartu Hijau sebagai Peningkatan Siswa Unggul Madrasah Aliyah Darul Huda Mayak Tonatan Ponorogo - Attarikhi, Ulul; Muasomah, Luluk; Ma'mun, Arif (LP. Ma'arif Janggan Magetan, 2024)
The Green Card is a Madrasah Tip to Improve the Quality of Education. Madrasahs play a major role in improving quality based on the renewal and creativity of madrasah managers who are dynamic, energetic, and have many ideas. Madrasah's task is to create highly competitive alumni academic and non-academic matters. This is implemented in the green card program. The green card program is a design or breakthrough implemented at Madrasah Aliyah Darul Huda Mayak Tonatan Ponorogo in developing superior students. This Green Card is a control book in the form of a module expected to improve or create superior students in the religious realm. This research aims to explain and describe the green card program as an Enhancement for Superior Students. This type of research is field research, which is included in qualitative research; the method for preparing or collecting data is by observing, interacting, understanding people in the environment, and documenting data. The data analysis technique used is analytical. The results of this research are that with the provision of the green card program, the competency diversity of students' practices and knowledge is said to be good and exceeds standards.